Growing of berehynia melon in the conditions of the southern steppe zone of Ukraine - Kalinin, O. V. (ТДАТУ, 2019)
Out that the Southern Steppe zone of Ukraine is one of the best zone for melon cultivation, but it is necessary to take into account the predecessors, built technology and irrigation system.
Keywords: melons; сорт Berehynia; melon cultivation